Fabrication, Development and Optimization of Mouth Dissolving Film of Ondansetron HCl by Natural Film Former - Ahire, Sandip B. (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: This study aimed to develop a mouth dissolving film of Ondansetron HCl. Materials and Methods: Solvent casting method is used, and various film forming polymers such as dried cassia tora gum, konjac gum, and PVP K30 in various concentrations were evaluated. The effect of independent factors, such as dried cassia tora gum, konjac gum, and PVP K 30 concentrations, on two dependent variables, such as disintegration time and percentage drug content, was examined using the 33 factorial design. The optimized formulation was identified based on a disintegration time of 5–30 s and a drug release exceeding 85%. Batches F5, F8, F-14, F20, F24, and F25 of the formulation show promising results. Results: As a result, each of these formulation batches were considered as optimized formulations and processes for in vitro dissolution testing. Batch F25 has a rapid disintegration time of 18.50 s and also the % drug release of 96.10% within 120 s. It contains 1% cassia tora gum, 1% konjac gum, and 1% PVP K30. Conclusion: From the results of this study, it can be interpreted that mouth-dissolving films of Ondansetron hydrochloride are feasible to prepare, provide quick onset of action, and have improved oral bioavailability using natural polymers.